Effects of sodium benzoate and licorice (Glycyrrhiza glabra) root extract on the heat resistance of escherichia coli O157 H7 in young coconut liquid endosperm - Salazar, Sesinanda Kristina P.; Gabriel, Alonzo A. (Quezon City College of Home Economics, University of the Philippines Diliman, 2012)
This study was conducted to determine the effects of sodium benzoate and licorice root extract on the heat resistance of E. coli O157:H7 in young coconut liquid endosperm. Results from the multi-level sensory evaluation process composed of a preliminary evaluation of the investigator, Focus Group Discussion (FGD) and a final Consumer Acceptance Test, showed that the most acceptable supplementation level for sodium benzoate and licorice root extract were 300 ppm and 250 ppm, respectively. The established limits of supplementation were used to generate sodium benzoate-licorice root extract combinations using two-factor Central Composite Design for the heat inactivation studies. Response surface analysis showed that only the individual linear effect of benzoate significantly influenced D55; and that at any level of licorice supplementation, the D55 decreased with increasing benzoate. This may be due to the relatively low concentrations of additives used in the study. The concentrations used were however based on the limits established by consumer acceptance tests. The study therefore recommended application of other hurdles to increase process lethality of low-temperature pasteurization processes.
Thesis Classification: P
Thesis (B.S. in Food Technology)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Coconut products; Food additives